Kepemimpinan Transformatif dan Budaya Inovasi sebagai Kinerja Perusahaan : Studi Kasus di Perusahaan Gojek - Umi Prasasti; Munawaroh Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Transformative leadership and a culture of innovation play an important role in determining company performance in today's digital era. One example of a company that has successfully implemented these two concepts is Gojek, a technology company based in Indonesia that has grown rapidly since it was founded in 2010. This research aims to analyze the role of transformative leadership and innovation culture in improving company performance, with a case study on Gojek . The research method used is descriptive qualitative in the qualitative research process, the emphasis is more on the subject's perspective, while theory is used as a guide by researchers to ensure that the research process is in accordance with the facts found in the field and helps to gain a deeper understanding. Gojek has succeeded in creating an ecosystem that supports collaboration, creativity and continuous technology development, which helps the company stay relevant and competitive in a very dynamic market.